2021
DOI: 10.3389/fcvm.2021.789325
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Role of Gut Microbiota in Amino Acid Metabolic Disturbances in Heart Failure Through Metagenomic Analysis

Abstract: Aims: Circulating amino acid (AA) abnormalities serve as predictors of adverse outcomes in patients with heart failure (HF). However, the role of the gut microbiota in AA disturbances remains unknown. Thus, we investigated gut microbial functions and their associations with AA metabolic alterations in patients with HF.Methods and Results: We performed whole-genome shotgun sequencing of fecal samples and mass spectrometry-based profiling of AAs in patients with compensated HF. Plasma levels of total essential A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…It is demonstrated that a significant positive correlation between the abundance of microbial genes involved in branched-chain AAs (BCAAs) biosynthesis and plasma BCCA levels in patients with HF. 11 It is interesting to discover that dapagliflozin enriched the valine and isoleucine in serum in our study, which is consistent with the result that empagliflozin switches myocardial fuel utilization away from glucose toward BCAA, thereby enhancing LV systolic function, and ameliorating adverse LV remodelling. 12 Moreover, compared with the Sham and the MI group, dapagliflozin treatment influenced the diversities and composition of faecal microbiota.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is demonstrated that a significant positive correlation between the abundance of microbial genes involved in branched-chain AAs (BCAAs) biosynthesis and plasma BCCA levels in patients with HF. 11 It is interesting to discover that dapagliflozin enriched the valine and isoleucine in serum in our study, which is consistent with the result that empagliflozin switches myocardial fuel utilization away from glucose toward BCAA, thereby enhancing LV systolic function, and ameliorating adverse LV remodelling. 12 Moreover, compared with the Sham and the MI group, dapagliflozin treatment influenced the diversities and composition of faecal microbiota.…”
Section: Discussionsupporting
confidence: 88%
“…The branched‐chain amino acid (BCAA) abnormalities serve as predictors of adverse outcomes in patients with HF, T2DM, and insulin resistance. It is demonstrated that a significant positive correlation between the abundance of microbial genes involved in branched‐chain AAs (BCAAs) biosynthesis and plasma BCCA levels in patients with HF 11 . It is interesting to discover that dapagliflozin enriched the valine and isoleucine in serum in our study, which is consistent with the result that empagliflozin switches myocardial fuel utilization away from glucose toward BCAA, thereby enhancing LV systolic function, and ameliorating adverse LV remodelling 12 …”
Section: Discussionsupporting
confidence: 81%
“…Patients with heart failure have lower plasma essential amino acid levels than healthy controls. The lack of Eubacterium and Prevotella leads to the decreased biosynthesis of essential amino acids (especially BCAAs and histidine) in patients with heart failure, on account of the reduced abundance of microbial genes related to essential amino acid biosynthesis ( 27 ). Prevotella-copri is lipopolysaccharide-producing bacteria, making it related to low-grade inflammation and the synthesis of BCAAs ( 28 ).…”
Section: Microbiota and Branched-chain Amino Acid-associated Metaboli...mentioning
confidence: 99%
“…In addition, the patients were not classified according to the type of heart failure, i.e., systolic or diastolic. Although a prior study conducted by Hayashi et al has refuted the role of ejection fraction in dysbiosis, further large-scale longitudinal studies are needed to exclude the effect of LVEF% on gut dysbiosis [26].…”
Section: Studies Involving Patients With Systolic and Diastolic Heart...mentioning
confidence: 99%